The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.54386/jam.v22i4.473
|View full text |Cite
|
Sign up to set email alerts
|

Influence of weather parameters on powdery mildew of mango inflorescence in humid tropics of South Gujarat

Abstract: The influence of environmental parameters on the development of powdery mildew caused by Oidium mangiferae Berthet on mango inflorescence was studied for seven consecutive years (2012-18) in humid tropics climatic conditions of South Gujarat. The disease incidence and severity (DIS), area under disease progress curve-AUDPC (A-value) and apparent infection rate (r-value) were recorded at panicle and fruit setting stages of the tree at weekly intervals. The correlation studies showed that incidence and severity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
1
4
0
Order By: Relevance
“…The present results can be used for better decision making well in advance to check the incidence and disease development in accordance with the weather. The present findings are corroborated by the works done by Gupta and Sharma (2009), Gupta and Sharma (2005) and Bana et al (2020).…”
Section: Effect Of Epidemiological Parameters On Powdery Mildew Of Ap...supporting
confidence: 91%
“…The present results can be used for better decision making well in advance to check the incidence and disease development in accordance with the weather. The present findings are corroborated by the works done by Gupta and Sharma (2009), Gupta and Sharma (2005) and Bana et al (2020).…”
Section: Effect Of Epidemiological Parameters On Powdery Mildew Of Ap...supporting
confidence: 91%
“…Similarly, relative humidity, rainfall and wind speed in the range of 85 -95%, 15.5 -20.75 mm and 1.0 -5.5 Km/h, respectively also found conducive for potato late blight disease and its development. Bana et al, (2020) showed that the disease incidence and disease severity of powdery mildew have significant negative relationship with morning relative humidity (r = -0.631; p<0.05 and r = -0.721; p<0.01) and average relative humidity (r = -0.766 and r = -0.787; p<0.01). The temperature (maximum and average) and evaporation showed positive relationship with disease incidence and severity of the disease.…”
Section: Multiple Regression Modelmentioning
confidence: 99%
“…Traditional statistical approaches (e.g., stepwise linear regression, multivariable linear regression, logistic regression, etc.) have shown limitations for outbreak predictions [15,[29][30][31]. Recent machine-learning approaches such as neural networks, decision trees, random forests, and support vector machines demonstrate an improved predictive accuracy for disease prediction [30,[32][33][34][35][36].…”
Section: Introductionmentioning
confidence: 99%